SUSTAINABLE CONCEPT FOR BORDER SETTLEMENT AT KAMPUNG ROMO KALISARI SURABAYA - Satya W. Santosa; Chintia P. Agnesi; Ricca A. Alamsyah (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2015)
The development of a city tend only to pay attention to the downtown area than in the border area. It can also be seen in the city of Surabaya, particularly in Sub-district Romo Kalisari which is a border kampung between Surabaya and Gresik. Border area is the main access from out of Surabaya to go to other cities and shows the identity of towns, especially to give a first impression on the city. But in Kampung Romo Kalisari, it has not been seen any effort to improve the quality of people.According to the theory used in this study, one of the things that are important in the development of the sustainable city is the economic improvement, particularly on the city's infrastructure. Border area also needs a management that supports the development of sustainable cities. Therefore, this study will provide concrete solutions on improving the city's infrastructure, such as transport and education facilities as well as the trade, which can be applied in the development of border kampungs in the Kampung Romo Kalisari, Surabaya.